Digital Education for Health Professions in the Field of Dermatology: A Systematic Review by Digital Health Education Collaboration - Xiaomeng Xu; Pawel Przemyslaw Posadzki; Grace E. Lee; Josip Car; Helen Elizabeth Smith (Medical Journals Sweden, 2018)
Digital health education is a new approach that is receiving increasing attention with advantages such as scalability and flexibility of education. This study employed a Cochrane review approach to assess the evidence for the effectiveness of health professions' digital education in dermatology to improve knowledge, skills, attitudes and satisfaction. Twelve trials (n = 955 health professionals) met our eligibility criteria. Nine studies evaluated knowledge; of those two reported that digital education improved the outcome. Five studies evaluated skill; of those 3 studies stated that digital education improved this outcome whereas 2 showed no difference when compared with control. Of the 5 studies measuring learners' satisfaction, 3 studies claimed high satisfaction scores. Two studies reported that when compared with traditional education, digital education had little effect on satisfaction. The evidence for the effectiveness of digital health education in dermatology is mixed and the overall findings are inconclusive, mainly because of the predominantly very low quality of the evidence. More methodologically robust research is needed to further inform clinicians and policymakers.